The impact of exercise on pregnancy: a comprehensive examination of benefits, risks, and considerations - Fayyazi Moghaddam, Shiva (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Pregnancy represents a crucial developmental stage characterized by notable physiological transformations. The significance of maintaining an active lifestyle during this period is widely acknowledged as a crucial element of prenatal health, providing a multitude of advantages for the overall well-being of both the mother and the fetus. This article offers a comprehensive examination of the role of exercise during pregnancy, delving into the physiological adjustments, suggested recommendations, and the potential advantages and drawbacks. Physical activity during pregnancy has been shown to have positive effects on weight management, the prevention of gestational diabetes and hypertensive diseases, as well as the enhancement of mood, body image, and sleep quality. There is a positive impact on fetal health outcomes, including ideal birth weight and enhanced heart rate patterns. Nevertheless, some medical issues and complications during pregnancy may necessitate adjustments or contraindications to activity. Although the advantages of exercise are well recorded, numerous pregnant women encounter obstacles when it comes to engaging in physical activity. Healthcare practitioners assume a pivotal role in resolving these problems and facilitating the promotion of safe and effective exercise among expecting moms. Additional investigation is required to clarify the most beneficial exercise recommendations, ascertain efficacious intervention approaches, and advocate for exercise as an essential element of prenatal healthcare.